Penggunaan Media Pembelajaran Interaktif Untuk Meningkatkan Minat Belajar Siswa - Ria Eka Sari; Fhery Agustin; Alfa Saleh; Rahma Tesya (Jurnal TUNAS, 2021)
Advances in information technology that are growing more rapidly have an impact on business competition in the information sector. The development of information technology has given rise to various types of activities based on digital devices supported by information technology, such as Multimedia, which now completely dominates all communication media that we often use. It can be seen, starting from mobile phones which have now become popular smartphones or smart phones through the Android and Apple operating systems, desktop applications to advertising media already using multimedia technology. Multimedia itself is in a computer environment and implies that the media is under the computer. Multimedia computers need to support more than one type of media based, among others: text, images, video, animation and audio. The purpose of this is that a computer can manipulate text and image data that are converted into multimedia data, so that it becomes a multimedia-based computer. To increase students' interest in learning by using interactive learning media, especially students at Private Vocational High School (SMK) PAB 8 Sampali Medan, this community service was carried out. As a result, the students' interest in learning has increased and they have started to get used to using interactive learning media.